Intellihire: An AI-powered interviewer for automated candidate selection - Tong, Qian Ru (2025)

(untitled)
The recruitment process has gone a long way to determine the success of organisations in today's highly competitive job market. Traditional interview techniques conducted by human recruiters can be time-consuming, require a huge number of resources, and often suffer from scheduling challenges and inconsistent evaluation criteria, which can influence the way decisions are made. These struggles can cause an inconsistency in the way candidates are evaluated and ultimately result poor hiring decision making. Artificial intelligence (AI) is the up-and-coming technological process that addresses these problems in recruitment. IntelliHire: an AI Interviewer for automated candidate selection is a project that envisions building an extensive Audio-visual enabled machine understanding engine to automate the shortlisting from resumes till scoring interview sessions. IntelliHire provides an inexpensive, time-effective and unbiased way to replace traditional interview methods. This innovation attempts to minimize the time and resources expected from a recruitment process while improving precision in selection as well as providing fairness for job applicants. Ultimately, IntelliHire has the potential to revolutionize the hiring process, providing organizations with a powerful tool to make more informed and objective hiring decisions.